SWANSTAT: a user-friendly web application for data analysis using shinydashboard package in R - Rizal Bakri; Bagus Sartono; Hazan Azhari Zainuddin; Laode Ahmad Sabil (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2020)
SWANSTAT is a user-friendly web application and free license that developed from the R programming language using shinydashboard Package. This research aims to create SWANSTAT was to streamline the routine workflow of data analysis so that users who are unfamiliar with R can perform the analysis interactively in a web browser with a cloud computing using a shiny server. The software development method used in this study is the SDLC with the waterfall model. The result of this research is the SWANSTAT software was developed using R by combining various packages and can be accessed online through various types of browsers on http://apps.swanstatistics.com. Besides, SWANSTAT consist of various features including the best visualization, the basis of statistical methods, help documents and tutorials. This research will continuously develop this application by enriching the latest statistical method, as well as improving the quality of features for data science needs.